1981
DOI: 10.1056/nejm198104233041701
|View full text |Cite
|
Sign up to set email alerts
|

Serum Alanine Aminotransferase of Donors in Relation to the Risk of Non-A,Non-B Hepatitis in Recipients

Abstract: To evaluate the incidence of post-transfusion hepatitis and factors influencing its occurrence, the Transfusion-Transmitted Viruses Study prospectively followed 1513 transfusion recipients from 1974 through 1979. The attack rate for non-A,non-B hepatitis was 10 per cent. The incidence of hepatitis was directly related to the alanine aminotransferase (ALT) level in blood donors. In recipients of multiple transfusions of blood that had no donor-ALT level above 29 IU per liter the attack rate was 6 per cent or le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
127
4

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 470 publications
(134 citation statements)
references
References 34 publications
3
127
4
Order By: Relevance
“…Many details of TTVS have been previously reported. [8][9][10] Briefly, from July 1974 through Octo- …”
mentioning
confidence: 99%
“…Many details of TTVS have been previously reported. [8][9][10] Briefly, from July 1974 through Octo- …”
mentioning
confidence: 99%
“…6 Aach et al have reported that high levels of serum alanine aminotransferase (ALT) may indicate viral hepatitis. 7 To reduce the incidence of post-transfusion hepatitis, the American Association of Blood Banks (AABB) formerly required that ALT be used to screen blood donors. 8 However, ALT screening lacks the sensitivity to detect all infectious units of blood.…”
mentioning
confidence: 99%
“…Serum enzyme activities regress as the injury progresses, which suggests that substantial serum AST or ALT does not necessarily refl ect cell death. AST is found in a wide variety of tissues beside liver, including heart, skeletal muscles, kidney, and brain, whereas ALT appears to be primarily located in the liver (38).…”
Section: Discussionmentioning
confidence: 99%